Motivating Potential Score (MPS) Determination Using By Job Characteristics And Its Relationship With Job Satisfaction Among Headquarters Staffs Of Tehran University Of Medical Sciences - Azadeh Ahmadzadeh Ghasab; Majid Heydari; Mohammad Ali Abbasi Moghaddam (Tehran University of Medical Sciences, 2013)
Background and Aim: Motivation and satisfaction of manpower are the most important variables in the field of organizational behavior and because of the strong relationship between these two variables with the job and organization productivity, it's necessary to look job characteristics as increasing factor of employee satisfaction and performance in redesigning jobs. The objective of this study was determining motivating potential score (MPS) of the jobs and survey the relation between MPS and job satisfaction in staff employees of educational and research deputy of TUMS (Tehran University of Medical Science). Materials and Methods: This was a cross-sectional and descriptive-analytical study. The research context was to staff employee of education and research deputy of TUMS. Sampling frame of the study was simple random sampling. Data collection method was a questionnaire. Reliability of the questionnaire was ascertained with pilot study with and confirm with Cranach's Alpha. T-test and Pearson correlation were the analytical methods. Results: The results showed the jobs of the study population have skill variety, task identity, task significance and potential motivation but haven't job authority and feedback. The findings showed there was significant relation between motivating potential power and its dimensions with the job satisfaction ( P<0.05 ). Conclusion : The job characteristic have great impact on the job satisfaction so this model can be used for redesigning the jobs to increase job satisfaction.